2022
DOI: 10.1088/1757-899x/1214/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle stability controller HiL validation on static simulator

Abstract: In the automotive world, Hardware in the Loop (HiL) methodologies are used to speed up the design and calibration process of the various mechatronics components installed on the vehicle. Installing production parts on advanced driving simulator enables the performance assessment in realistic scenarios, including a test driver earlier in the design process. The scope of this work is to evaluate the effect of ABS and ESC system, replicating their influence on the steering wheel. A brake by wire production system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The unit functionalities have been tested in [41], comparing the responses and behaviors on the static simulator with respect to a real vehicle, proving its effectiveness on a previously validated vehicle model.…”
Section: Braking Unitmentioning
confidence: 96%
“…The unit functionalities have been tested in [41], comparing the responses and behaviors on the static simulator with respect to a real vehicle, proving its effectiveness on a previously validated vehicle model.…”
Section: Braking Unitmentioning
confidence: 96%
“…The brake bench has been installed on the driving simulator thanks to the collaboration with the company Meccanica 42. The simulator setup is the same as reported in [6,11,12,13]: for the scope of this work, the simulator can be described as composed by four main parts: the driver cockpit, the real time simulator, the EPSiL steering bench, and the Braking bench. With this specific setup, the driver can then test both steering and brake unit hardware, equipped with stock ADAS functionalities.…”
Section: Real-time Driving Simulator Setupmentioning
confidence: 99%
“…Yin et al [22] proposed a system to predict the pedal feel at the time of braking. The pressure changes inside the braking system lead to changes in the feeling of the braking pedal [23]. To overcome this problem, the pedal feel is studied in relation to pressure changes to stabilize those changes by applying a fully decoupled brake-by-wire system [18], [23].…”
Section: Introductionmentioning
confidence: 99%
“…The pressure changes inside the braking system lead to changes in the feeling of the braking pedal [23]. To overcome this problem, the pedal feel is studied in relation to pressure changes to stabilize those changes by applying a fully decoupled brake-by-wire system [18], [23]. Mullner et al [24] suggested a Simulink model that would be used as the last verification step before applying any proposed system.…”
Section: Introductionmentioning
confidence: 99%